Pengaruh Ekuitas Merek Terhadap Keputusan Menabung Nasabah Tabungan Ebatara Pos di Kantor Layanan Setara Kantor Kas (KLKK) Pariaman - Yomi Dwita Aprilia; Verinita Verinita (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2019)
Abstract : This research investigated the impact of brand equity on customer saving decision at Ebatara Pos in KLKK Pariaman.  The data obtained through questionnaire. The samples were drawn from 105 customers who have saving in Ebatara Pos.  The data analyzed by using SPSS 20.0. Sampling technique in this study was done by using purposive random sampling The analysis technique used is multiple regression. In this research there are 2 variable: those are independent variable which are brand awareness, brand association, perceived quality and brand loyalty, the dependent variable which is saving decision. The findings indicated that brand awareness has positive and not significant impact on customer saving decision. For brand association, perceived quality and brand loyalty have positive and significant impact on customer saving decision at Ebatara Pos